Doktrin priviti ke jus quasitum tertio: Rasional peralihannya - Sakina Shaik Ahmad Yusoff,; Suzanna Mohamed Isa, (Fakulti Undang - Undang, 2007)

(untitled)
Doctrine of privity and its application has invited numerous criticisms amongst academician and members of the judiciary. On the other hand, there are also those who support and relentlessly defend its existence. Nevertheless, this doctrine, which has survived over a century, has recently encountered a shift in paradigm brought about by time and need of commerce. The void that has resulted is now being filled with another doctrine that is not at all alien to the spectrum of contract law – jus quaseitum tertio. With the background of changes occurring in the United Kingdom and several Commonwealth countries, this paper will endeavor to rationalize the shift that needs to occur in the Malaysian contract law, pertaining to doctrine of privity